Agricultural Research in Government Agencies in Latin America; A Preliminary Assessment of Investment Trends - International Service for National Agricultural Research (International Service for National Agricultural Research, 1997)
Severe economic crisis has affected many Latin American countries throughout the 1980s. Economic growth stagnated, while indebtedness increased sharply. The structural adjustment programs that were consequently implemented usually required substantial cuts in government spending, including public spending on agricultural R&D. In addition, budgets have been very volatile in real terms due to extreme high inflation. As a result, public agricultural research agencies throughout Latin America have had to deal with declining and unstable budgets and a substantially more critical government attitude when it comes to paying the research bill during the past 10-15 years. The purpose of this paper is to update an earlier account of agricultural research investments trends and patterns in Latin America (Pardey, Roseboom, and Anderson 1991) and document the investment trends experienced by the national agricultural research organizations between 1971 and 1991. It is a detailed, technical account which provides a fully-referenced set of time series in the appendix as well as a list of references used to construct the dataset. This paper starts with a brief discussion of methodological issues in section 2, followed by an overview of the investment trends for some 12 Latin American INIAs (national agricultural research organizations) in section 3. Together, these INIAs represent the bulk of public agricultural research in the region. Light will be shed on how deep budgets have been cut as well as how INIAs have responded in terms of downsizing research staff. Section 4 provides some more detailed characteristics of research staff and expenditure, while section 5 provides an estimation of total public agricultural research investments for each country and a cross-country comparison of investment intensity. The paper ends with a 'conclusions' section.